Plasma deposition of parylene-C film - Song, Zhiquan; Im, Ju-Hee; Ko, Hyuk; Park, Jun-Hee; Lee, Ga-Yeon; Kang, Min-Jung; Kim, Moo-Hwan; Pyun, Jae-Chul (ELSEVIER, 2021)
A new method that uses plasma energy for the deposition of parylene-C films is presented. The equipment and instrumentation for the plasma deposition of parylene-C films were developed and constructed by combining evaporation and plasma-generating units. The plasma deposition of parylene-C films consists of three steps: evaporation, decomposition of the parylene-C dimers using plasma, and deposition of the film. The entire deposition process from evaporation to deposition was designed to be completed within 20 min for a parylene-C film with a thickness of less than 200 nm. The thickness of the parylene-C film was controlled in the range of 100-200 nm by adjusting the amount of parylene-C dimer as well as the plasma energy. The parylene-C films prepared by plasma deposition were characterized and compared with those obtained using the conventional pyrolysis method. The comparison included the chemical properties (chemical functional groups, atomic compositions) and their physical properties (density, crystallinity, absorption in the visible wavelength range, surface roughness and contact angle).